Inventory planning and control in Dataran Setar Sdn. Bhd. - Nor Nadhira, Ahmat Azemi (2016)
Inventory management is the most important business process for every production company as it relates to purchases, logistic, sale and also services. It is related to control the stock of raw materials for the company’s production. The main objectives of this thesis are to calculate sales data from the company, to optimize the quantity of raw materials and to analyze the best alternative solution to the company’s problem. By using production planning and control method, the company’s problem was solved. Step by step of production planning and control method such as forecasting, aggregate planning, master production schedule, materials requirement planning, bill of materials and order policy are to determine when and how many of each items should be order.